Characterization of kefir-like beverages produced from vegetable juices. (March 2016) - Corona, Onofrio; Randazzo, Walter; Miceli, Alessandro; Guarcello, Rosa; Francesca, Nicola; Erten, Hüseyin; Moschetti, Giancarlo; Settanni, Luca
Abstract: The aim of this work was to develop new non-dairy fermented beverages using vegetable juices as fermentable substrates. Carrot, fennel, melon, onion, tomato and strawberry juices underwent back-slopping fermentations, carried out by water kefir microorganisms. Results indicated that lactic acid bacteria and yeasts were capable of growing in the juices tested. Melon juice registered the highest numbers of microorganisms. Almost all juices underwent a lactic fermentation. After fermentation, there was observance of a decrease of the soluble solid content and an increase of the number of volatile organic compounds. In particular, esters were present in high amounts after the fermentation, especially in strawberry, onion and melon, whereas carrot and fennel registered a significant increase of terpenes. The concentration of alcohols increased, while that of aldehydes decreased. Changes in colour attributes were registered. Strawberry, onion and tomato juices retained a high antioxidant activity after fermentation. The overall quality assessment indicated that carrot kefir-like beverage (KLB) was the product mostly appreciated by the judges. These findings support the further development of vegetable KLBs with additional benefits and functional properties. Highlights: Six vegetable juices allowed the development of water kefir microorganisms. The highest microbial counts were registered during transformation of melon. All fruit juices underwent lactic and alcoholic fermentation. Carrot kefir-like beverage was mostly appreciated by the judges. Melon KLB showed safety issues due to Enterobacteriaceae and pseudomonads.